2011
DOI: 10.1111/j.1349-7006.2011.01939.x
|View full text |Cite
|
Sign up to set email alerts
|

YN968D1 is a novel and selective inhibitor of vascular endothelial growth factor receptor‐2 tyrosine kinase with potent activity in vitro and in vivo

Abstract: Angiogenesis is an important process in cell development, especially in cancer. Vascular endothelial growth factor (VEGF) signaling is an important regulator of angiogenesis. Several therapies that act against VEGF signal transduction have been developed, including YN968D1, which is a potent inhibitor of the VEGF signaling pathway. This study investigated the antitumor activity of YN968D1 (apatinib mesylate) in vitro and in vivo. YN968D1 potently suppressed the kinase activities of VEGFR-2, c-kit and c-src, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
433
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 469 publications
(446 citation statements)
references
References 27 publications
12
433
0
1
Order By: Relevance
“…Therefore, development of novel inhibitors that selectively inhibit VEGFR-2 but not the other VEGFR family members might be an attractive approach for cancer therapy [3] . Our results demonstrate that DW10075 exhibits selective inhibition against VEGFR-2 with high potency, which is even lower than apatinib, as reported previously (IC 50 1 nmol/L) [27] , clearly indicating that DW10075 possesses comparable VEGFR-2 inhibitory activity and much higher selectivity than the known selective VEGFR inhibitors.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Therefore, development of novel inhibitors that selectively inhibit VEGFR-2 but not the other VEGFR family members might be an attractive approach for cancer therapy [3] . Our results demonstrate that DW10075 exhibits selective inhibition against VEGFR-2 with high potency, which is even lower than apatinib, as reported previously (IC 50 1 nmol/L) [27] , clearly indicating that DW10075 possesses comparable VEGFR-2 inhibitory activity and much higher selectivity than the known selective VEGFR inhibitors.…”
Section: Discussionsupporting
confidence: 51%
“…Apatinib is a highly selective VEGFR-2 inhibitor that was approved for the treatment of gastric cancer in China in 2014. In addition to VEGFRs, apatinib also exhibits moderate inhibition of RET, c-kit, and c-Src [27] . In this report, we identified DW10075 as a novel, highly selective inhibitor of VEGFRs that is almost equally as potent as axitinib and apatinib.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally it inhibits also RET, c-KIT and c-SRC and has some effect on EGFR, HER-2 and FGFR [98]. In preclinical models, apatinib was active against a broad spectrum of tumors [98].…”
Section: Apatinibmentioning
confidence: 99%
“…Apatinib is a TKI selectively targeting VEGFR-2 [58,59]. A phase I clinical trial showed that this agent has antitumor activity in Chinese patients with metastatic GC [60].…”
Section: Apatinibmentioning
confidence: 99%